Surrogate Motherhood in Russia and in the World: Legal Issues and Vectors of Sociological Research - Denisova, Maria (Journal of Economic Sociology, 2018)
The round table ‘Surrogate Motherhood in Russia and in the World: Legal Issues and Vectors of Sociological Research’ was held at the Laboratory for Studies in Economic Sociology at the Higher School of Economics on February 22, 2018. At the present time, the theme of surrogate motherhood is highly deliberated not only in Russia but also abroad. Despite the fact that there is a clear worldwide trend of legalizing the service, the question of its legitimization and normalization remains open. In that regard, there is a need for sociological research covering various aspects of surrogate motherhood. The reports presented at the round table were devoted to the complex, multifaceted consideration of the surrogate motherhood market. The participants’ presentations covered a wide range of topics, starting with the adjustment policies of the medical service and constructing a discourse around it, and ending with an overview of the potential risks to the well-being of children born with the help of surrogate programs. Some reports also included the first results of empirical research which allowed participants to focus on the specifics of surrogate motherhood in Russian society. The aim of the round table was to clarify the specifics and the problems of surrogate motherhood in Russia, as well as to determine the vectors of sociological research in this field. The keynote speakers of the session were Olga Khazova (Institute of State and Law, Russian Academy of Sciences, and member of the UN Committee on the Rights of the Child), Maria Denisova (LSES NRU HSE), Oksana Dorofeeva (LSES NRU HSE), Olga Doletskaya (NRU HSE), Elena Berdysheva (LSES NRU HSE).